MON-LB035 Adrenal Venous Sampling in the Lateralization of Acth-Independent Cushing Syndrome With Bilateral Adrenal Masses: A Case With a 5-Year Follow-Up - Kang, Yu Mi (J Endocr Soc, 2020)
Background Nearly 25% of adrenal Cushing syndrome (CS) patients with bilateral adrenal masses have unilateral hypercortisolism, making localization crucial for surgical planning. Since there is no standardized protocol for adrenal venous sampling (AVS) in lateralizing adrenal hypercortisolism, we share our experience with a case of CS with bilateral adrenal masses in which lateralization via AVS permitted unilateral adrenalectomy. Clinical Case A 59-year-old woman with hypertension, hyperlipidemia, and prediabetes was hospitalized for worsening back pain and hypertension. Her BMI was 26.5 kg/m(2), BP 173/93 mmHg, HR 73/min, she was anxious, diaphoretic, and hirsute. Glucose was 118 mg/dL and HbA1c 6.6%. Abdominal computed tomography revealed a type B aortic dissection with both right (6.1 x 3.1cm and 3.6 x 2.4cm), and left (largest 1.7 cm) sided adrenal masses. Plasma and 24 hour-urine metanephrine, normetanephrine and catecholamines, as well as plasma renin and aldosterone levels, were normal. AM cortisol on three different occasions was 21.30, 20.70, and 21.30 mcg/dL. Midnight cortisol was 17.8 mcg/dL, and 24-hour urine free cortisol on two occasions was 163 mcg (urine volume 3.4L with creatinine 1.14) and 99.2 mcg (urine volume 1.15L). After 1mg dexamethasone her AM ACTH and cortisol were <5 and 18.70 mcg/dL, respectively. Preoperative AVS was performed and 8mg of dexamethasone was administered the night prior to ensure ACTH suppression during the procedure, and epinephrine was measured to ascertain adequate adrenal vein cannulation. Cortisol levels (in mcg/dL) from the common iliac, right and left adrenal veins were 14.7, 61.5, and 23.5 at 0 minute and 15.2, 61.0, and 22.7 at 2 minutes, respectively. Epinephrine levels (in pg/dL) from the common iliac, right and left adrenal veins were 42, 577, and 3225 at 0 minutes, and 46, 718, and 2989 at 2 minutes. Despite higher epinephrine levels from the left adrenal, the cortisol ratio of the right adrenal vein to peripheral vein was 4.18 with the right-to-left ratio of 2.59 and 2.68 at 0 and 2 minutes, suggesting hypersecretion of cortisol from the right adrenal gland. Unilateral right adrenalectomy revealed a 5.6 cm adrenal adenoma arising in a background of adrenal cortical hyperplasia. Morning postoperative cortisol was 2.2 mcg/dL. She was placed on hydrocortisone and tapered over a 10-month period with remission maintained for more than 3.5 years post-operatively. Conclusion This case demonstrates the safety, usefulness, and necessity, of AVS in localizing cortisol production when bilateral adrenal masses are present. In addition, this case suggests that the use of high dose dexamethasone and measurement of catecholamines may be helpful for more accurate interpretation. More data on AVS in CS patients with bilateral adrenal masses is needed so a well-validated and standardized CS-specific ACS protocol can be developed.